Protective effects of acetylcholine on hypoxia-induced endothelial-to-mesenchymal transition in human cardiac microvascular endothelial cells - Li, Zhiyang; Li, Xuelian; Zhu, Yeqian; Chen, Qiushi; Li, Bingong; Zhang, Fengxiang (Molecular and cellular biochemistry, 2020)
Endothelial-to-mesenchymal transition (EndMT) has been reported as a key factor in myocardial fibrosis. Acetylcholine (ACh), a neurotransmitter of the vagus nerve, has been confirmed to exert cardio-protective properties with unclear mechanisms. In this study, the specific markers of cell injury, EndMT, inflammation, and autophagy were measured. We found that treatment with ACh prevented hypoxia-induced cell viability reduction and apoptosis in human cardiac microvascular endothelial cells (HCMECs). Additionally, our results indicate that pre-treatment with ACh significantly suppresses hypoxia-induced EndMT and NF-κB activation in HCMECs. ACh also reduced hypoxia-inducible factor (HIF)-1ɑ protein levels under hypoxia. Knock down of HIF-1ɑ enhanced the inhibitory effect of ACh on NF-κB activation. The NF-κB-specific small molecule inhibitor BAY 11-7082, prostaglandin E2, and LY294002 prevented hypoxia-induced EndMT. Moreover, our data show that hypoxia triggers autophagy in HCMECs, and ACh significantly upregulates autophagy activity. Pre-treatment of HCMECs with 3-methyladenine or chloroquine partially reversed ACh-induced EndMT inhibition. These results suggest that ACh may confer protection against hypoxia-induced EndMT through the inhibition of NF-κB and the induction of autophagy.